A convenient eco-friendly system for the synthesis of 5-sulfenyl tetrazole - Fortes, Margiani P. (2014)
The use of CeCl3·7H2O in polyethyleneglycol 400 (PEG-400), as an efficient and eco-friendly promoter system for the convenient synthesis of 5-sulfenyl tetrazoles derived from indoles and pyrroles, is reported. The synthesis entails the [3 + 2] cycloaddition reaction of NaN3 with 3-thiocyanato indoles (including 3,3′-di-thiocyanato-1H,1H′,2,2′-biindoles) and 2-thiocyanato pyrroles. The thiocyanates were conveniently obtained by the oxone-mediated thiocyanation of differently substituted starting indoles, 1H,1H′,2,2′-biindoles and N-aryl pyrroles with NH4SCN. The scope and limitations of the transformation were also studied.